Menstrual cycle and Exercise - Algul, Sermin; Alp, Busra; Ozcelik, Oguz (Progress in Nutrition, 2022)
Menstruation is the biological rhythm that women experience every 28±7 days. Menstruation is defined as an endometrial rash and continues from menarche to menopause. There are increasing and decreasing hormonal changes during this cycle. Ovarian follicles and hormones (estrogen and progesterone) secreted from the corpus luteum cause some cyclic changes in the endometrium. Changes in the wall of the uterus constitute the endometrial cycle, which is called the menstrual cycle or menstrual period.Exercise is a physical activity that affects many systems such as the heart and musculoskeletal system and the health and fitness of the individual. As it affects many systems, this cyclical event, which is performed regularly by women, is also effective on menstruation. Menstruation phases, exercise type, exercise duration and continuity, and exercise intensity affect this cycle. This review will evaluate how different exercises and intensity affect the menstrual cycle.